Magazine on urban agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Urban Agriculture Magazine PO Box 64 3830 AB Leusden Netherlands Fax: +31 33 494 07 91 Email: ruaf@etcnl.nl Website: http://www.ruaf.org/